The role of the flexibility of the financial structure of companies in avoiding the financial crisis - an analytical study in the commercial banking sector listed on the Iraqi Stock Exchange for the period from (2006-2015): دراسة تحليليه في (قطاع المصارف التجارية) المدرجة في سوق العراق للأوراق المالية للمدة من ((2015-2006 (1) - Taher Mohsen Mansour Al-Ghalbi,; Haider Hamoudi Ali Al-Zubaidi, (Iraqi Journal for Administrative Sciences, 2024)
The financial crisis one of the basic characteristics of the present era, And that threaten the businesses and sustainability, Search aims to delve into the implications of the current financial crisis and to identify its causes and its consequences and choose the appropriate ways to address them through the diagnosis of the impact of the financial flexibility to avoid financial crisis, Model premise and conceptual study was developed through extensive and in-depth review of the literature relevant to the three axes of the study and of financial flexibility (leverage ratios, liquidity ratios) as the independent variable, the financial crisis (capital adequacy ratio, profitability ratios, bad debt ratios, the proportion of loans to deposits ) as the dependent variable, The research community commercial banks listed on the Iraq Stock Exchange, has been chosen as the (10) ten commercial banks as a sample for the study consisted of time series study to (10) ten years (2006-2015). Data for statistical analysis has been subjected by employing a package of ready-made software, particularly software (SPSS, V.23). The results proved that there was a significant effect of financial flexibility and its role in the reduction of the financial crisis, a relationship, and research found to a set of conclusions, notably to explain the financial flexibility of the financial crisis on the macro level and at the level of sub-indices.